The Response of Grain Yield and Root Morphological and Physiological Traits to Nitrogen Levels in Paddy Rice - Xin, Wei; Liu, Hualong; Zhao, Hongwei; Wang, Jingguo; Zheng, Hongliang; Jia, Yan; Yang, Luomiao; Wang, Xinpeng; Li, Jiaming; Li, Xianwei; Lei, Lei; Zou, Detang (Frontiers in Plant Science, 2021)
Rice (Oryza sativa L.) is an important crop in China. Although it is known that its yield is restricted by nitrogen (N) supply, the response of the root system to N supply specifically has not been systematically explored. This study aimed to investigate the effect of N uptake on grain yield to clarify the relationships between root morphophysiological traits and N uptake, and to understand relation between phytohormones and root morphophysiological traits. Two N-efficient absorption cultivars (NEAs) and two N-inefficient absorption cultivars (NIAs) were grown in the field, and three N conditions, deficient N (60 kg ha–1), intermediate N (180 kg ha–1), and sufficient N (240 kg ha–1), were applied during the growing season. The results showed higher dry matter and grain yield in NEAs than in NIAs, which was mainly attributed to increased N uptake in the mid- and late growth stages under all N conditions. And NEAs have different root regulation methods to obtain higher N accumulation and yield under different N supply conditions. Under lower N conditions, compared with NIAs, NEAs shown greater total root length, root oxidation activity, and root active absorbing surface area and smaller root diameter owing to higher indole-3-acetic acid and cytokinin content and lower 1-aminocyclopropane-1-carboxylic acid content in the early growth stages to respond to low N stress faster, laying a morphophysiological basis for its high N-uptake capacity in the mid- and late growth stages. Under higher N conditions, NEAs had higher root oxidation activity and root active absorbing surface area for N uptake and yield formation owing to higher abscisic acid and cytokinin content in the mid- and late growth stages, which improved the seed setting rate, thereby increasing the rice grain yield. These results suggest that NEAs can optimize the morphophysiological characteristics of roots through phytohormone regulation to adapt to different nutrient conditions, thereby promoting N accumulation and yield formation in rice.